Dukungan Keluarga Dan Tingkat Kecemasan Ibu Anak Tunanetra Di Sekolah Luar Biasa - Zahro Winda Kusuma; Dwi Soelistyoningsih; Ika Arum Dewi Satiti (Media Husada Journal Of Nursing Science, 2026)
Abstract Mothers of children with visual impairment often experience psychological distress due to caregiving demands and concerns about their children’s future, which may increase the risk of anxiety. Family support is an important factor influencing mothers’ psychological well-being. This study aimed to examine the relationship between family support and anxiety levels among mothers of visually impaired children at SLB A, B, and D Negeri Kedungkandang, Malang City. This study employed a correlational analytic design with a cross-sectional approach. The population consisted of all mothers of visually impaired children registered at SLB A, B, and D Negeri Kedungkandang, totaling 30 respondents, selected using total sampling. Data were collected using the Perceived Social Support from Family (PSS-Fa) questionnaire to measure family support and the Hamilton Rating Scale of Anxiety (HARS) to assess anxiety levels. Data analysis was performed using Spearman Rank correlation with a significance level of 0.05. The results showed that most respondents had moderate to low levels of family support and experienced moderate to severe anxiety. Spearman correlation analysis revealed a significant negative relationship between family support and anxiety levels (p < 0.05), indicating a moderate to strong correlation. Higher family support was associated with lower anxiety levels among mothers of visually impaired children. This study concludes that family support plays a crucial role in reducing anxiety among mothers of visually impaired children. Strengthening family support, particularly emotional support and family involvement in caregiving, is essential to improve mothers’ psychological well-being.